Effects of different light conditions on ammonium removal in a consortium of microalgae and partial nitrifying granules. (15th March 2020) - Akizuki, Shinichi; Kishi, Masatoshi; Cuevas-Rodríguez, Germán; Toda, Tatsuki
Abstract: Ammonium removal by a coupling process of microalgae ( Chlorella sorokiniana ) with partial nitrifying granules was evaluated in batch reactors illuminated in a wide range of light intensities (0, 100, 450, and 1600 μmol photons m −2 s −1 ). Ammonium oxidation performance for different light exposure time showed that the granules had a light stress tolerance at 1600 μmol photons m −2 s −1 for up to 12 h, but continuous illumination induced severe inhibition on nitrifying bacteria thereafter. Ammonium removal efficiencies at the end of tests were 66%, 62%, 5%, and −10% (due to ammonification) for 0, 100, 450, and 1600 μmol photons m −2 s −1, respectively. The nitrogen mass balance shows co-occurrence of microalgal growth taking up 24% of fed ammonium and nitrifying bacteria oxidizing 38% of fed ammonium at 100 μmol photons m −2 s −1, while both nitrification and microalgal growth are inhibited at light intensity above 450 μmol photons m −2 s −1 . In comparing results from this study with previous results, it was found that the ammonium removal pathway, i.e., nitrification or microalgal uptake, is regulated more strongly by daily average light intensity than by instantaneous light intensity. Empirical model equations to estimate the oxygen balance in consortium reactors categorized the effect of daily average light intensities on process performance as follows: (i) below 27 μmol photons m −2 s −1 : insufficient oxygen for nitrification; (ii) 27 to 35: sufficient oxygen for nitrification via nitrite; (iii) 35 to 180: sufficient oxygen for nitrification via nitrate; (iv) above approximately 200–300: oversaturated dissolved oxygen, excess free ammonia and/or intensive light inhibitions. Graphical abstract: Image 1 Highlights: Granules had a light stress tolerance at 1600 μmol photons m −2 s −1 for up to 12 h. Observed co-occurrence of algae growth and nitritation at 100 μmol photons m −2 s −1 . NH4 + removal pathway was regulated most strongly by daily average light intensity. Empirical models show consortia via NO2 − works well at 27–35 μmol photons m −2 s −1 .